Utilizing Digital Storytelling Structure for Developing an Electronic Traditional Game Gobak Sodor - Bambang Pudjoatmodjo; Amir hasanudin Fauzi; Sazilah Salam; Tio Ahmad Muluk; Dendy Syahreza Maulana (IJAIT (International Journal of Applied Information Technology), 2021)
Gobak Sodor is a traditional game that came from Indonesia. Gobak Sodor is also known as a different name in Indonesia and Malaysia, such as Panjang tangan in Riau-Sumatra, Asing in Makassar, Galah Asin in West Java, and Galah Panjang in Malaysia. Gobak Sodor is a game that is played in two groups and has a rule that one group must prevent the opponent through the line back to back. However, Indonesia's open area has gradually reduced so that people difficult to play gobak Sodor. The loss of open land for playing Gobak Sodor and game technology advances make children slowly forget the gobak sodor. In the present time, technology is common for people to support their daily life activities. One of technology implementation form is electronic game, where peoples can play without the limitation of time and space. The electronic game also give pleasure and fun as much as conventional game activities. With the form of electronic game, this research develop a game application which implements all of the gobak sodor rules. Where the players can play the gobak sodor using their mobile device and without the trouble to play on a field or open space. Using electronic game for playing Gobak Sodor gives people satisfaction, awareness. In the hope that this will preserves the traditional game Gobak Sodor. The survey found that 80% of people have an interest to play The Gobak Sodor game.